M.I. PLATOV'S PERSONALITY IN THE EVALUATION OF E. P. SAVELYEV - E. Steglenko (Гуманитарные и юридические исследования)
The article focuses on the research on the Don ataman (Cossack chieftain) Matvey Platov by the Don historian of the early 20th century Evgraf Savelyev. One of the outstanding Don Cossacks' military commanders and administrators has always attracted the attention of various researchers. Recently his endeavors have been broadly recognized in various forms of historic memory. However, some aspects of his biography and their perception by the Cossacks are still insufficiently studied. One of the brightest examples of the formation of the image of Platov in Cossack historiography is the work of E.P. Saveliev Ataman M.I. Platov and Foundation of the Town of Novocherkassk (in 1805). It was published in Novocherkassk in 1906 and is a serious contribution to the study of the multifaceted activities of Ataman Platov. However, this work was practically ignored in Soviet and Russian historiography. Meanwhile, E. P. Savelyev is a typical representative of the intellectual environment of the Don Cossacks of the early twentieth century. Her views are widely demanded in the modern Cossack movement, which gives additional relevance to the study. E.P. Savelyev characterizes the milestones of the Platov's life - from an auspicious officer of the times of Catherine the Great to the hero of the Patriotic War of 1812. Certain notorious episodes of the Platov's biography (embezzlement accusation, coninement in Peter and Paul's Fortress) are described by E.P. Savelyev in his work but are considered a misunderstanding and the result of the court's scheming. E.P. Savelyev singles out administrative work and political flexibility of the ataman. He especially demonstrated these qualities when decision to found Novocherkassk was made. Such conclusions about M. I. Platov to a great extent correspond to his historical image. The scientiic novelty of the article consists in understanding the work of E. P. Savelyev «Ataman M. I. Platov and the foundation of Novocherkassk (in 1805)» as an insuficiently studied historiographic source in the context of analyzing the tradition of historiography of the early twentieth century.